Do Personality Traits Matter in Preferences of Translation Strategies? - Haldun Vural (Research in Social Sciences and Technology- OpenED Network, 2022)
Translation is closely related to languages, linguistics, pragmatics, sociolinguistics, culture etc. and because of these relations, there are also a lot of theories which give importance either to source language or target language. Linguistic and other features of the source and target texts have been examined for years. But translator is an important element with an important role in translation process as well, and the influence of translators’ personality traits on their translation has been emphasized. Therefore, the aim of the current study is to investigate whether there are relations between translators’ personality characters and their translation strategy preferences. The BFI Test (Big Five-Factor Inventory) is administered to 28 English Translation and Interpreting students at Cappadocia University to determine the personality traits of the participants. Then they are asked to choose one of the suggested translations in accordance with the translation model. The data are analyzed through SPSS (v. 22). The findings indicate that there are significant relationships between personality traits of participants and their use of translation strategies. According to results, agreeableness personality trait has a significant relationship with borrowing strategy, openness and neuroticism have significant relationships with modulation strategy, and conscientiousness has a significant relationship with adaptation strategy. Only extraversion does not correlate significantly with any of the strategies.